Munasabah Akhlak Surah Al-Isra' Ayat 23-25 Terhadap Moral Islam dalam Kitab Tafsir Kontemporer - Fauziah Nur Ariza; Nasution , Nida Holita; Rafiah Dian Safitri; Risyda Luthfiyah; Abdul Rafi Alrasyid; Syafiq Hamdi Ahmad Lubis; Irfansyah; Devina Tanjung (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to examine the relationship (munasabah) between the moral verses in Surah Al-Isra', verses 23-25, and the Islamic moral values ​​reflected therein. The study was carried out using a contextual analysis approach by tracing the meaning and relationships between verses, in order to find moral messages that are thematically connected. Surah Al-Isra' presents the concept of morals which includes human relationships with Allah, with each other, and with oneself. The results of the analysis show that the arrangement of the verses in this surah is not random, but has a regular meaning that strengthens moral values ​​such as justice, responsibility, politeness and social concern. By understanding the munasabah, it can be seen that the moral teachings in Surah Al-Isra' also have relevance in self-management and moral management of the daily lives of Muslims.